The procedural and attitudinal contents in the learning of Basic Biomedical Sciences and the days after the COVID-19 pandemic - Luis Alberto Mass Sosa; Sandra Cecilia William Serrano; Milagros Lisett León Regal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
The declarative, procedural and attitudinal contents that each of the sciences contribute to the program of the Biological Bases of Medicine discipline, give rise to contradictions in a space of disciplinary development, where they have their own rhythm of subordination and integration. The objective of this work is to answer some questions that have the background, the rupture between the evaluation to be carried out ¨in certain circumstances of the teaching process¨ and the objectives and methods conceived for such purposes; fundamentally promoted, based on the curricular adjustments made due to the COVID-19 pandemic. Its authors consider necessary a greater presence of procedural and attitudinal content in the programs of the subjects of this discipline, based on better management of the curriculum and the implementation of a conception of learning much more adjusted to past, present and future demands, that allows students to appreciate through the process and not only the result, the value of what they build in educational activities where they express values and university attitudes appropriate to major social problems.